The motion law of oil droplets and bubbles in air flotation-cyclone - WANG Wei; BAI Xu; CHU Xiaodan; ZHAO Xiang; MA Xueliang; LIN Wei; GONG Cheng; YU Jiuyang (Gongye shui chuli)
Microbubble air flotation cyclone technology is an innovative and efficient separation method combining flotation separation and cyclone separation. Using this technology for oil-water separation, the effects of dissolved gas water microbubbles, cyclone fields, and flocculants on separation efficiency were investigated. High-speed imaging technology was utilized to study the interaction between microbubbles and oil droplets, as well as between microbubbles and flocs. The results showed that dissolved gas water microbubbles significantly reduced oil-water separation time, cutting it by 50% compared to static settling in pure water. At an initial oil-water mixture concentration of 400 mg/L, the optimal experimental conditions for the combined flotation+cyclone+flocculant process were: Oil-water mixture to dissolved gas water volume ratio of 1∶4, cyclone velocity of 370 r/min, composite flocculant ratio (PAC∶CPAM) of 2∶1. Under these conditions, the final oil concentration in wastewater was less than 10 mg/L, meeting the requirements of the Integrated Wastewater Discharge Standard (GB 8978-1996). In static water conditions, the average projected area of microbubble-floc aggregates was approximately six times that of microbubble-oil droplet aggregates, indicating that the addition of flocculants was conducive for improving oil-water separation. Interaction experiments demonstrated that, compared to pure water static settling, oil content in wastewater decreased by 38.7%, 71.4%, and 76.5% after treatment using microbubble air flotation, flotation+cyclone, and flotation+cyclone+flocculants, respectively. The final oil-water separation effectiveness was in order of three-factor combination>dissolved gas water microbubbles +cyclone field>dissolved gas water microbubbles alone.